PENGARUH KEPUASAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN LEMBAGA PENGEMBANGAN DAN SERTIFIKASI BATU MULIA (LPSB) DI MARTAPURA KABUPATEN BANJAR - Eni Hairany; Marijati Sangen (Universitas Lambung Mangkurat, 2014)
This study has the objective of identifying and analyzing the influence of satisfaction and trust on customer loyalty LPSB Martapura Banjar District. Research location conducted in LPSB Martapura Banjar Regency. The population of this research is all the customers who use the services LPSB in requesting certificates, as well as scrap in 2012, according to the data contained in the report LPSB in 2012 as many as 124 people . Based on the results of hypothesis testing, with multiple linear regressions, get that the satisfaction and confidence significantly positive effect on customer loyalty LPSB Martapura Banjar District. Partially, satisfaction and confidence significantly positive effect on customer loyalty. Between two variables, satisfaction variable is a variable that is the dominant influence on customer loyalty LPSB Martapura Banjar district